PWE-163 The changing demographic of the bariatric patient in the UK – the experience of a high through put bariatric unit. (22nd June 2015) - Bennett, JMH; Carr, W; Jennings, N; Balupuri, S; Mahawar, K; Small, PK
Abstract : Introduction: With the publication of the 3 year NBSR results a key statement is the increasing age and weight of the average Bariatric surgical patient. This has been coupled with an increase in surgery for male patients across the UK. With this has come a larger burden of associated co-morbid conditions. We examined our bariatric practice to further consider this change. Method: Analysis of a prospective database of all bariatric seminar attendances which includes demographic and weight data. Data is presented from 2008–2014. Results: Overall we have seen an increase in attendance at our seminar and progression to surgery, tempered by the delay caused by the introduction of Tier 3 (Table 1 ). Over the 6 year period assessed the average BMI at both seminar and surgery has decreased. The proportion of the sexes has remained constant. A trend of increasing age at seminar and surgery is seen, although the increase is less in operated patients. The average BMI at surgery decreased from 52 to 49Kgm 2 for males but increased for women from 42 to 45 Kgm 2 . Conclusion: Mean BMI has deceased for both male and female patients over time for both the seminar attendance and patients proceeding to surgery, contra to the data published by the NBSR. This may reflect a shift in the targeting of surgery in our centre towards patients with the maximum potential gain in terms of co-morbidity resolution and extended life span. It may also reflect a greater appreciation of the prevalence of morbid obesity and options for treatment leading to earlier referral from general practice. Disclosure of interest: None Declared.